Alternate routes to sustainable energy recovery from fossil fuels reservoirs. Part 1. Investigation of high-temperature reactions between sulfur oxy anions and crude oil. (15th October 2021) - Jin, Xiao; Wu, Jia; Silva, Renzo C.; Huang, Haiping; Zhang, Zhihuan; Zhong, Ningning; Tutolo, Benjamin M.; Larter, Steve
Graphical abstract: Highlights: H2 S is a potential energy vector to deliver carbon free fuel from petroleum. The polysulfide species can promote the alteration of petroleum on human timescales. S species could oxidize both aromatic and saturated hydrocarbons efficiently. Abstract: The world is undergoing a substantial transition in its energy supply. Examining the possibilities to recover and use fossil fuel energy without emitting carbon dioxide to the surface, H2 S was considered as an alternative energy vector to deliver a carbon free fuel from petroleum reservoirs to the surface. In this study, we investigated the high P-T chemical oxidation of crude oil with a suite of inorganic sulfur compounds. Tested inorganic sulfur compounds can be ordered by their ability to promote chemical changes to the oil matrix with the concomitant production of hydrogen sulfide, with a reactivity series, listed in order of decreasing reactivity as: S 0  > S2 O3 2− ~ S4 O6 2− > SO3 2− > SO4 2− . The reaction mechanisms proposed in the study also light on likely key intermediate reactants and the geological timescale process of thermochemical sulfate reduction. Polysulfide species (containing S-S bond structures), such as thiosulfate and tetrathionate, may be reactive intermediates during the redox reaction. However, the early stage of thermochemical sulfate reduction may also involve labile organic sulfur functional groups converting to more stable molecules with aromatic structural units, such as dibenzothiophenes (DBT) and benzonaphthothiophenes (BNT). The apparent formation of saturated fatty acids and O2, NO and NO2 aromatic heteroatom species indicates the oxidation of saturated and aromatic hydrocarbons or heteroatom compounds. The oxidation of aromatic species may lead to aromatic ring-opening, followed by decarboxylation forming CO2 as final products.